Clinical and Epidemiologic Features of Diarrheal Disease due to Aeromonas hydrophila and Plesiomonas shigelloides Infections Compared with Those due to Vibrio cholerae Non-O1 and Vibrio parahaemolyticus in Bangladesh. (24th September 2012) - Klontz, Erik H.; Faruque, Abu S. G.; Das, Sumon K.; Malek, Mohammed A.; Islam, Zhahirul; Luby, Stephen P.; Klontz, Karl C.
Abstract : Using data from the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr, b) from 1996 to 2001, we compared the clinical features of diarrhea in patients with stool specimens yielding only A. hydrophila (189 patients; 1.4% of 13, 970 patients screened) or P. shigelloides (253 patients) compared to patients with sole V. cholerae non-O1 infection (99 patients) or V. parahaemolyticus infection (126 patients). Patients exhibited similar frequencies of fever (temperature >37.8°C), stools characterized as watery, and stools containing visible mucus. Dehydration was observed more often among patients with V. parahaemolyticus or V. cholerae non-O1 infection. Compared to patients infected with V. parahaemolyticus, those with A. hydrophila, P. shigelloides, or V. cholerae non-O1 infection were less likely to report visible blood in the stool and, on microscopic examination, less likely to exhibit stool red blood cell and white blood cell counts exceeding 20 cells per high power field. The proportion of patients reporting subjective cure at the time of discharge was significantly smaller for those infected with V. parahaemolyticus. These findings suggest that A. hydrophila and P. shigelloides produce diarrheal disease that is less severe than that resulting from infection with V. cholerae non-O1 or V. parahaemolyticus.